STUDENTS’ PERCEPTION ON DARING LEARNING WHILE QUARANTINE: A QUALITATIVE CASE STUDY - Yulandari, Evi Safitri (Journal of Languages and Language Teaching, 2020)
This study was aimed to know the perception of the second semester of English department students? in Institut Pendidikan Nusantara Global when they are have to use daring learning as a media for their learning process when they did the quarantine because of the covid-19 virus. The researcher did a qualitative case study with the total 32 students? involved as well as participant. This study used several data instrument in gathering the data dealing with the question of the study, i.e: analysis of students? writing test in the form of writing essay and interview. The researcher were also give a detailed description of a case study ? its definition, some classifications, and several advantages and disadvantages ? in order to provide a better understanding of this widely used daring study. The data were then analyzed whether their writing results were reaching the minimum standard or not and were the students doing well in daring study or not. From the comparisons, the researcher makes a conclusion in the form of descriptions whether the students' of English department in institut pendidikan nusantara global enjoy their daring study while quarantine or not.